Effect of isobutyl methacrylate and methacrylic acid eluted from chairside denture hard reliners on enzymatic cellular antioxidants: An in vitro study in human primary buccal mucosal fibroblasts - Sivanesan Karthikeyan Jagdish; Anbazhagan Ganeshkumar; Rajaraman Shakila; Shyam Singh; Balasubramanian Jesudas; Sivanesan Karthikeyan (Wolters Kluwer Medknow Publications, 2017)
Aim: This study was conducted with the objective to evaluate the cytotoxicity of monomers isobutyl methacrylate (IBMA) and methacrylic acid (MA) in human buccal mucosal fibroblast primary cell culture and to study their effect on cellular enzymatic antioxidants-glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT). Materials and Methods: The tissue for fibroblast cell culture was harvested from oral buccal mucosa of a healthy donor. Fibroblast cells were plated at a density of 1 × 104 cells per well in 96-well tissue culture plates. Cells were exposed to various concentrations of IBMA and MA. The cell viability and various enzyme activities were evaluated 24 h after exposure to the above treatments. All tests were done in triplicate. Cell viability was assessed by trypan blue dye exclusion assay and all enzyme activities were done using assay kits from Cayman Chemicals, Ann Arbor, USA. Results: At all concentrations tested a statistically significant decrease in viability was observed in IBMA- and MA-treated cells. Around 42% cells were viable at the highest test concentration of IBMA (80 μmol/L) and only 20% cells were viable at the highest dose (144 μmol/L) of MA exposure (P < 0.05). Dose-dependent decrease in the GPx and SOD activities was observed in cells treated with IBMA and MA (P < 0.05). CAT activity was not detectable in the controls. However, a fall in CAT activity was detected in cells exposed to IBMA and MA at all concentrations tested (P < 0.05). Conclusion: IBMA and MA leaching out from the chairside denture hard reliners are cytotoxic on human buccal fibroblast primary cell cultures. This could be due to the oxidative stress caused by the generation of reactive oxygen species which is evidenced by the fall in activities of antioxidant enzymes (GPx, SOD, and CAT) and cytotoxicity.